Condomínio de agroenergia: potencial de disseminação na atividade agropecuária - Schuch, Sérgio Luís (2012)
This paper aims to draw attention to the large volume of residual biomass of the animal and its potential for biogas production and commercialization in western Paraná. Stressing the importance to address animal waste not as an environmental problem of difficult solution, but with a new approach, the residual biomass raw material animal, obtained without direct cost and without the need for specific investments in its production. The generation of bioenergy through the implementation of digesters in rural property, for processing and marketing of energy from biogas, signals as a new business opportunity and regional income. The comparison of results between marketing biogas equivalent to liquefied petroleum gas to electric power generation, demonstrates the advantage to marketing as gas.